Desinfecção fotoeletrocatalítica de águas contaminadas com Candida Parapsilosis utilizando eletrodos de W/WO3 em tratamento fotoeletrocatalítico - Souza, Bárbara Camila de Araújo [UNESP] (2015)
The access to quality water, free of pathogenic microorganisms and potentially harmful to the community is a constant challenge of being human. Among the various pathogenic microorganisms, the presence of those belonging to the kingdom Fungi has drawn attention, especially in hemodialysis water, due to the consequences that the presence of these and their respective mycotoxins causes to an immunocompromised patient. The aim of this study was to investigate the capability of W/WO3 as photoanode in disinfection systems using photoelectrocatalysis in water contaminated by Candida parapsilosis. For this, tungsten trioxide was synthesized using electrodes via electrochemical anodization by the growth of WO3 films in tungsten foil as a substrate. The prepared electrode was characterized morphologically and electrochemically and was subsequently applied in a photoelectrochemical system. The FEMSEM image showed a formation of a homogeneous film in the surface foil with nanopores around 100 nm. There was obtained a band gap of 2.5 eV calculated from Tauc's plot of the Kubelka-Munk method and photocurrent observed in NaCl 0.1 molL-1 was equal to 19 mA. Studies of C. parapsilosis degradation in NaCl 0.1 molL-1, pH 7, the potential equal to 1.5V and irradiating UV-Vis and Vis, previously optimized conditions, showed the death of yeast at 30 seconds of treatment. There was no significant formation of active chlorine under the conditions employed just as there is formation of chlorate and perchlorate ions during photoelectrocatalytic degradation. For photoelectrocatalytics measurements in the dialysate, there was microbial death in about 5 minutes and removal of total organic carbon at around 73% and 45% for acidic and basic solutions, respectively.